Adopting a cognitive information processing approach to increase students’ career maturity - Qamaria, Rezki Suci; Astuti, Fidia (Jurnal Cakrawala Pendidikan, 2021)
The results of a survey on students in a university in Kediri found the fact that students are still confused and do not have any idea about their future careers even though the study period is almost complete. This might be because they lack knowledge about career options that are appropriate to their field of study, feel less confident about their abilities, lack self-awareness related to their potential, and do not yet know how to prepare themselves for the work world. These phenomena illustrate the lack of student career maturity. This condition might cause an increase in the unemployment rate or job mismatch. Against this backdrop, we designed and implemented strategies to overcome these problems using a Cognitive Information Processing approach. In particular, we conducted Focus Group Discussions (FGD) with students, implemented career counselling, and carried out career socialization. This research used a pre-experimental design, particularly a one-group pretest and posttest design. The result shows that students experienced a significant increase in their career maturity. Students now have a better picture of career options that match their educational background, have short-term and long-term planning related to career readiness after completing education and have confidence in their abilities or potential.